Self-reported incidence and age of onset of chronic comorbid medical conditions in adults aging with long-term physical disability. Issue 3 (July 2016) - Smith, Amanda E.; Molton, Ivan R.; Jensen, Mark P.
Abstract: Background: Adults with long-term disability are living longer and may experience accelerated aging. More information is needed to understand the incidence of chronic comorbid medical conditions in this population. Objective: To examine the incidence, prevalence, age of onset and predictors of five chronic conditions in a sample of adults with long-term physical disability. Methods: Longitudinal self-report surveys were mailed to 1594 adults with multiple sclerosis, muscular dystrophy, post-polio syndrome or spinal cord injury twice, 3.5 years apart. Survey questions assessed demographics (date of birth, sex, income, disability type, height/weight), self-reported diagnosis of coronary heart disease, hypertension, arthritis, diabetes and cancer, and health behaviors (alcohol use, smoking, physical activity). Results: Over the course of the study, the most commonly reported new onset chronic comorbid medical condition was arthritis (percent incidence = 14%), followed by hypertension (9%) and cancer (7%). Report of a new condition was greatest in adults aged between 56 and 65 years, and risk factors included greater BMI, waist circumference, and the presence of another chronic comorbid medical condition at baseline. Conclusions: Chronic comorbid medical conditions are prevalent in persons with long-term physical disability. Midlife appears to be the period of greatest risk for onset of a new condition, and risk for incidence increases in the presence of other chronic comorbid medical conditions. Modifiable risk factors include BMI and waist circumference. Future research should explore whether changes in modifiable factors at midlife or earlier (e.g., diet, exercise) would help prevent or delay onset of comorbid conditions in this population.